Exclusive Gut Flagellates of Serritermitidae Suggest a Major Transfaunation Event in Lower Termites: Description of Heliconympha glossotermitis gen. nov. spec. nov - Radek, Renate; Meuser, Katja; Strassert, Jürgen F H; Arslan, Oguzhan; Teßmer, Anika; Šobotník, Jan; Sillam-Dussès, David; Nink, Ricardo A; Brune, Andreas (The Journal of eukaryotic microbiology, 2018)
The guts of lower termites are inhabited by host-specific consortia of cellulose-digesting flagellate protists. In this first investigation of the symbionts of the family Serritermitidae, we found that Glossotermes oculatus and Serritermes serrifer each harbor similar parabasalid morphotypes: large Pseudotrichonympha-like cells, medium-sized Leptospironympha-like cells with spiraled bands of flagella, and small Hexamastix-like cells; oxymonadid flagellates were absent. Despite their morphological resemblance to Pseudotrichonympha and Leptospironympha, a SSU rRNA-based phylogenetic analysis identified the two larger, trichonymphid flagellates as deep-branching sister groups of Teranymphidae, with Leptospironympha sp. (the only spirotrichosomid with sequence data) in a moderately supported basal position. Only the Hexamastix-like flagellates are closely related to trichomonadid flagellates from Rhinotermitidae. The presence of two deep-branching lineages of trichonymphid flagellates in Serritermitidae and the absence of all taxa characteristic of the ancestral rhinotermitids underscores that the flagellate assemblages in the hindguts of lower termites were shaped not only by a progressive loss of flagellates during vertical inheritance but also by occasional transfaunation events, where flagellates were transferred horizontally between members of different termite families. In addition to the molecular phylogenetic analyses, we present a detailed morphological characterization of the new spirotrichosomid genus Heliconympha using light and electron microscopy.
Keywords: Gastrointestinal Microbiome; Parabasalidea; symbiont; Evolution; RNA, Protozoan; ultrastructure; Microscopy, Electron, Scanning; Isoptera; zvířata; Parabasalia; RNA ribozomální; Trichomonadea; RNA protozoální; mikroskopie elektronová rastrovací; RNA, Ribosomal; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Spirotrichosomidae; střevní mikroflóra; Animals; molecular phylogeny